Intracerebral haemorrhage-induced injury progression assessed by cross-sectional photoacoustic tomography - Yang, Jinge (Biomed Opt Express, 2017)
In this study, we in vivo examined injury progression after intracerebral haemorrhage (ICH) induced by collagenase in mice using cross-sectional photoacoustic tomography (csPAT). csPAT displayed high resolution with high sensitivity for ICH detection. The PAT images obtained showed high correlation with conventional histologic images. Quantitative analysis of the hematoma areas detected by csPAT showed high consistency with the neurologic deficit score (NDS). By utilizing the dual-wavelength method, the development of the hemoglobin area was monitored. Our results indicated that noninvasive csPAT can be used to track the dynamic progression of post-ICH, and to evaluate therapeutic interventions in preclinical ICH models.